Recipient Age Predicts 20-Year Survival in Pediatric Liver Transplant. (17th September 2022) - Keeling, Stephanie; McDonald, Malcolm F.; Anand, Adrish; Dunson, Jordan; Williams, Elizabeth; Zhang, Theodore; Hickner, Brian; Galván, Nhu Thao Nguyen; Mahony, Christine O'; Goss, John A; Rana, Abbas
Abstract : Introduction . Pediatric liver transplant recipients have demonstrated excellent long-term survival. The purpose of this analysis is to investigate factors associated with 20-year survival to identify areas for improvement in patient care. Methods . Kaplan–Meier with log-rank test as well as univariate and multivariate logistic regression methods were used to retrospectively analyze 4, 312 liver transplant recipients under the age of 18 between September 30, 1987 and March 9, 1998. Our primary endpoint was 20-year survival among one-year survival. Results . Logistic regression analysis identified recipient age as a significant risk factor, with recipients below 5 years old having a higher 20-year survival rate (p < 0.001 ). A preoperative primary diagnosis of a metabolic dysfunction was found to be protective compared to other diagnoses (OR 1.64, CI 1.20–2.25). African-American ethnicity (OR 0.71, CI 0.58–0.87) was also found to be a risk factor for mortality. Technical variant allografts (neither living donor nor cadaveric) were not associated with increased or decreased rates of 20-year survival. Conclusions . Our analysis suggests that long-term survival is inversely correlated with recipient age following pediatric liver transplant. If validated with further studies, this conclusion may have profound implications on the timing of pediatric liver transplantation.